ENERGY EFFICIENCY IMPROVEMENT IN AIR CONDITIONERS AFTER REPAIR AND MAINTENANCE PROCESS - Zuraidah Tharo; Rahmaniar; Trio Putra Agung Wijaya; Feri Karyanta Bangun; Budi Hartono (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the improvement in energy efficiency of air conditioning (AC) systems after repairs and routine maintenance. The use of unmaintained AC units leads to an increase in energy consumption, which results in higher operational costs. This research measures the changes in electrical power consumption and cooling capacity at two locations: the village office and a residential house. The results show a 25% reduction in power consumption at both locations after the repairs were made, as well as an 8.6% improvement in cooling capacity at the village office and a 13.6% improvement at the residential house. The study also identifies factors that affect energy efficiency, such as refrigerant leaks and component cleanliness. The findings of this study are expected to provide insights into the importance of maintenance and repairs for AC systems to enhance energy efficiency